Tantalize : Kieren's story - Smith, Cynthia Leitich (Smith, Cynthia Leitich. Tantalize series, 2011)
Werewolf-in-training Kieren is torn between joining an urban wolf pack and staying to protect his human best friend (and love interest) Quincie, whose restaurant is in danger of morphing into a vampire lair.